POLITICAL MYTHS IN THE SYMBOLIC SPACE OF RUSSIAN ELITES: FEDERAL AND REGIONAL ASPECTS (A NORTH CAUCASIAN CASE STUDY) - SALGIRIEV, Ali; BETILMERZAEVA, Maret; -Emi SHAMSUEV, Magomed; OSMAEV, Abbaz (CENTRAL ASIA AND THE CAUCASUS, 2018)
The political and administrative elites, acting amid social, political, and economic changes and facing rising conflict potential in their countries, have no choice but to tap into the full potential of symbolic politics as an important instrument of power. Their continued presence in the corridors of power depends, to a great extent, on their ability to influence public opinion, which is especially important during election campaigns. To succeed, the elites have to use symbolic interactions and political myths as the most efficient instrument of brainwashing. The authors have described the technologies and practices used to construct functional political myths.The social and cultural crisis into which the country had slipped in the first post-Soviet years, economic problems, and seats of ethnopolitical conflicts made the use of barely verified information practically inevitable. The authors have analyzed the sources, means, and instruments used to form and adjust public opinion. In democratic countries, political systems are formed by and rely on independent media, balanced editorial policies, and the resolute rejection of unfounded or harmful information by the public. We live in “real virtuality” (Manuel Castells): real politics is still burdened by the Soviet heritage of myths firmly rooted in people’s minds and their readiness to accept utopian ideas. The elites, meanwhile, are building up conspiracy theories, searching for external and internal enemies, and offering simplified and irrational explanations of social and political processes unfolding in the country. New myths are created and promoted amid the country’s mounting isolation, multiplying sanctions, and economic problems.The authors have identified the sources of an obvious mythologization of public space as the alienation of citizens from real politics and their inertia, as well as the specifics of the binary structure of consciousness rooted in the past. In their minds, people separate politics from the economy and are more concerned about the country’s greatness and might than about standards of living. No wonder that the citizens of Russia are proud of the country’s armed forces, space exploration, heroic history, and sports achievements and are pushing mundane issues aside. As expected, political elites are associated with the country’s might, its international status, etc.Ideological preferences and adherence to different schools produced several debatable opinions about the role of the political elites. It is commonly believed that they play a negative or even destructive role. To arrive at an unbiased conclusion, the article analyzes their resource base, algorithms of their activities, political and governing functions, and related strategies. The article concludes with recommendations on lowering the level of mythologization of public consciousness by implementing at least some elements of civil society.